Esports players, got muscle? Competitive video game players` physical activity, body fat, bone mineral content, and muscle mass in comparison to matched controls - DiFrancisco-Donoghue, J.; Werner, W. G.; Douris, P. C.; Zwibel, H. (Journal of Sport and Health Science, 2022)
Background Esports players, like traditional athletes, practice for long hours and, thus, are vulnerable to the negative health effects of prolonged sitting. There is a lack of research on the physical activity and the health ramifications of prolonged sitting by competitive players. The purpose of this study was to investigate activity levels, body mass index (BMI), and body composition in collegiate esports players as compared to age-matched controls.